Implementation of Good Corporate Governance in Cooperatives: A Study in Yogyakarta Indonesia - Kunti Sunaryo; Zuhrohtun Zuhrohtun; Siwi Hardiastuti. E.K.; Indra Kusumswardhani; Heri Susanto (Pelopor Publikasi Akademika, 2023)
This study aims to measure the implementation of corporate governance (GCG) practices in cooperatives. Cooperatives are seen as having a great influence on the country's economic growth. Corporate governance if carried out properly will have an impact on the growth of the existing cooperative which in turn will provide welfare to its members. Good cooperative management must carry out GCG practices that are accountability, effectiveness, responsibility, transparency, fairness, and independence which are the basic principles of a good organization. This study uses cooperative members and administrators as research objects. This research uses a descriptive approach. The results of data processing show that the questionnaires distributed are valid and reliable so that it can be concluded that the average results of the measurement of accountability, effectiveness, responsibility, transparency, fairness and independence in cooperatives show a number above 4 so that it can be concluded that GCG practices in cooperatives are running very well